Blood platelet behaviour during infusion of an Intralipid based intravenous feeding mixture. Issue 677 (March 1982) - Burnham, W. R.; Cockbill, S. R.; Heptinstall, S.; Harrison, S.
Abstract : Blood platelet behaviour was studied in six patients during infusion of an Intralipid-based intravenous feeding mixture. Lower concentrations of sodium arachidonate were required to induce platelets to aggregate and to undergo a release reaction during intravenous feeding than were required before or after intravenous feeding. This change was not due to a change in serum albumin level. The platelet behaviour that was induced by adenosine diphosphate or by adrenaline remained unchanged during intravenous feeding.